Optimization of bio-oil blends in gasoline engines for enhanced efficiency and emissions reduction: A response surface methodology approach - Apip Amrullah; Obie Farobie; Herry Irawansyah; Abdul Ghofur; Lusi Ernawati; Misbahuddin (Results in Engineering, 2024)
The escalating global demand for energy, coupled with growing environmental concerns, necessitates the exploration of cleaner fuel alternatives. Bio-oil, characterized by its renewability and potential to mitigate emissions, has emerged as a viable candidate. This study focuses on optimizing bio-oil concentrations in gasoline engines to enhance operational performance while reducing pollutant emissions. Employing Response Surface Methodology (RSM), the investigation evaluates the effects of varying bio-oil-gasoline blends on engine performance metrics, fuel consumption, and exhaust emissions. Experiments were conducted using a single-cylinder, four-stroke gasoline engine with bio-oil concentrations of 5 %, 10 %, and 15 %. The results identified an optimal bio-oil concentration of 9–10 % and an injection pressure range of 220–230 bar Under these conditions, the Brake Thermal Efficiency (BTE) increased by 31.1 %, and the Brake Specific Fuel Consumption (BSFC) was reduced to 274.4 g/kWh, indicating enhanced fuel efficiency. Emissions analysis demonstrated a 45 % reduction in carbon monoxide (CO) and a 50 % decrease in hydrocarbon (HC) emissions at a bio-oil concentration of 10 %, with nitrogen oxide (NOx) emissions controlled below 110 ppm at higher bio-oil levels. These findings suggest that the optimized bio-oil blend significantly improves engine efficiency while minimizing environmental impact, positioning bio-oil as a promising solution for cleaner and more sustainable energy production.